Business acumen and why it matters - Sutton, Kyra Leigh (Henry Stewart Talks, 2021)
What is business acumen, Showing business acumen in interviews, Demonstrating business acumen on the job, Example of a business acumen solution, Millennial leaders who showed business acumen